KAJIAN KESIAPAN PEMENUHAN API PADA BUSN YANG BERKANTOR PUSAT DI SURABAYA - Setiawan, Djoko Budi; Haryati, Sri (Jurnal Keuangan dan Perbankan, 2008)
The purpose of the research was to provide empirical evidence on the variablesthat affected Tier 1 capital. The variables used to assess financial performance were financialratios: profitability, assets quality, solvability and growth. While the visualization of the positionof bank financial performance was analyzed by Radar Method. The result of the research wassupposed to take decisions in implementing the Indonesian Banking Architecture. The researchpopulation was Indonesian Commercial Banks whose headquarter was in Surabaya, and thesecondary data were the publication of bank financial statements of thirteen time perceptionswhich were in period June 2000 June 2006. Binary Logistic Regression with stepwise methodand Radar Method was used for instrument analysis. The result of the research showed thatfrom eighteen variables which were analyzed, there were only five variables representing thesignificant determination of Tier 1 capital. Referring to the four analyzed financial ratios,these five variables refered to profitability (two variables), asset quality (two variables), andgrowth (one variable). These significant variables and Radar analysis were used by the banksthat had not fulfill Tier 1 capital yet to make a decision on whether they realized their actionplan or implement consolidation program.